THE MANAGEMENT OF RELIGION-BASED CHARACTER EDUCATION AT THREE MADRASAH IBTIDAIYAH IN GORONTALO PROVINCE - Hasbi, Muhammad; Sonhadji, Ahmad; Huda, Muhammad; Arifin, Imron (IJRDO- Journal of Educational Research, 2017)
The main objective of this qualitative research was to describe the management of relogion-based character education at the Madrasah Ibtidaiyah (MI) in Gorontalo Province, Indonesia. Location of the research were in MI Terpadu Al Ishlah, MI Muhammadiyah, and MI Almourky. The research findings indicate that (1) planning activities of character education at Madrasah was based on the vision and mission of the institution which was set up by school boards and teachers to deciced program and subject contents of character education, (2) the implementation of character education was initiated by encouraging the teaching of core values employing comprehensive approach such as: (a) by integrating of core values into all subjects matter, (b) by implying in all extra-curricular activities, (3) by immersing into Madrasah culture; (3) assessment of character education was conducted via (a) direct observation and (b) evaluation on academic activities (grade report). The finding of the research suggest that the role of education management in the context of character education program in Madrasah is very important to handle the program more effective and efficient in order that character education can come up and align with the target and objective of the government’s objective. Therefore, it is in need of Madrasah principals and school boards’ creativity and innovation to develop and implement character education program professionally, instead of doing the program is just because of routine activity. The effective use of school facilities and empowering work ethos, school culture and family will significantly support the program of character education at these mentioned schools.